Comparison of Flavonoid Intake Assessment Methods Using USDA and Phenol Explorer Databases: Subcohort Diet, Cancer and Health-Next Generations—MAX Study - Lanuza, Fabian; Bondonno, Nicola P.; Zamora-Ros, Raul; Rostgaard-Hansen, Agnetha Linn; Tjønneland, Anne; Landberg, Rikard; Halkjær, Jytte; Andres-Lacueva, Cristina (Frontiers in Nutrition, 2022)
Flavonoids are bioactive plant compounds that are widely present in the human diet. Estimating flavonoid intake with a high degree of certainty is challenging due to the inherent limitations of dietary questionnaires and food composition databases. This study aimed to evaluate the degree of reliability among flavonoid intakes estimated using four different approaches based on the two most comprehensive flavonoid databases: United States Department of Agriculture (USDA) and Phenol Explorer (PE). In 678 individuals from the MAX study, a subcohort of the Diet, Cancer and Health-Next Generations cohort, dietary data were collected using three 24-hour diet recalls over one year. Estimates of flavonoid intake were compared using flavonoid food content from PE as 1) aglycones (chromatography with hydrolysis), 2) aglycones transformed (converted from glycosides by chromatography without hydrolysis), 3) as they are in nature (glycosides, aglycones and esters), and 4) using flavonoid content from USDA as aglycones (converted). Spearman, intra-class correlation (ICC) and weighted kappa (K) coefficients were calculated for the reliability analysis. When comparing PE total aglycones to USDA total aglycones, there was a moderate reliability when a continuous variable was used (ICC: 0.73, 95% confidence interval (CI): 0.70-0.76) and an excellent reliability when flavonoid intake was modeled as a categorical variable (K: 0.89, 95% CI: 0.88-0.90). The degree of reliability among all methods of estimated flavonoid intakes was very similar, especially between database pairs, especially for the flavanol subclass. While larger differences were observed for flavone, flavonol and isoflavone subclasses. Our findings indicate that caution should be taken when comparing the results of the associations between flavonoid intakes and health outcomes from studies, when flavonoid intakes were estimated using different methods, particularly for some subclasses.